2002
DOI: 10.1038/nature00804
|View full text |Cite
|
Sign up to set email alerts
|

Subendothelial retention of atherogenic lipoproteins in early atherosclerosis

Abstract: Complications of atherosclerosis are the most common cause of death in Western societies. Among the many risk factors identified by epidemiological studies, only elevated levels of lipoproteins containing apolipoprotein (apo) B can drive the development of atherosclerosis in humans and experimental animals even in the absence of other risk factors. However, the mechanisms that lead to atherosclerosis are still poorly understood. We tested the hypothesis that the subendothelial retention of atherogenic apoB-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
331
0
15

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 823 publications
(352 citation statements)
references
References 27 publications
6
331
0
15
Order By: Relevance
“…Recent data suggest that apo B 48 and apo B 100 containing lipoproteins are probably equally atherogenic [96]. Both apoproteins can bind effectively to proteoglycans, the former via a newly identified binding segment of apo B 48 masked in apo B 100 [96] and the latter via a different domain [97]. In concert postmeal metabolic excursions comprise a cluster of potentially highly atherogenic perturbations that could be more important in terms of damaging the arterial wall than those due to hyperglycaemia [76].…”
Section: Is Postprandial Lipidemia a Hazard?mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data suggest that apo B 48 and apo B 100 containing lipoproteins are probably equally atherogenic [96]. Both apoproteins can bind effectively to proteoglycans, the former via a newly identified binding segment of apo B 48 masked in apo B 100 [96] and the latter via a different domain [97]. In concert postmeal metabolic excursions comprise a cluster of potentially highly atherogenic perturbations that could be more important in terms of damaging the arterial wall than those due to hyperglycaemia [76].…”
Section: Is Postprandial Lipidemia a Hazard?mentioning
confidence: 99%
“…The conformation of apo B 100 is distinct between the LDL subspecies and this is reflected in the different exposure of apo B 100 on the surface of LDL particles. The key difference is that specific segments which mediate the binding of apo B 100 to proteoglycans are exposed on the surface of small dense LDL particles [96,97,101,103].…”
Section: Is Postprandial Lipidemia a Hazard?mentioning
confidence: 99%
“…25 Reduced apo B binding to intimal proteoglycans markedly attenuates atherosclerosis in mice. 26 Apo B is a large and intensively studied protein with globular and ␣-helical amphipathic domains and ␤-sheets. 27 Apo B-100 (4536 residues) is produced in the liver, where it is assembled into very low density lipoproteins before secretion into plasma.…”
mentioning
confidence: 99%
“…LDL retention at the subendothelial level is one of the first events triggering atherosclerosis, with the concurrent involvement of SMC for the disease onset and progression (20,41). It has been shown that, together with macrophages, AoSMC overloaded with cholesterol contribute to foam cell formation (21), highlighting the emerging role of this cell type in early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%